Impact of antiemetic steroid use on survival in small cell lung cancer patients receiving immune checkpoint inhibitors and chemotherapy - Soh Mee Park; Jonghyun Jeong; Yu Jung Kim; Ju-Yeun Lee (Scientific Reports)
Abstract Immune checkpoint inhibitors (ICIs) combined with conventional cytotoxic agents have become the new standard of care for extensive-stage small cell lung cancer (SCLC). The platinum-based agents in these regimens are highly emetogenic, necessitating prophylactic antiemetic steroids. This study evaluated the impact of prophylactic antiemetic steroid use on survival outcomes and efficacy in patients with SCLC undergoing combination therapy. Using data from the National Health Insurance Service of Korea database, patients treated with atezolizumab, etoposide, and carboplatin between 2020 and 2022 were categorized by antiemetic steroid dosage. Primary outcomes included overall survival (OS) and time to next treatment (TTNT), assessed using multivariable Cox proportional hazards models. After propensity score matching, 2,116 patients were categorized into low-dose (0–12 mg), moderate-dose (13–24 mg), and high-dose (25–36 mg) groups. Median OS was 10.2 months (interquartile range [IQR] 5.2–18.5), and median TTNT was 8.6 months (IQR 4.8–15.5), with no significant differences among groups. Subgroup analysis revealed increased mortality associated with higher antiemetic steroid doses in patients concurrently receiving non-antiemetic steroids. Although antiemetic steroids did not significantly impact survival outcomes overall, reducing their dosage in patients already on steroid therapy for other indications is recommended.